Bone health in post-menopausal patients with breast cancer treated with aromatase inhibitors: factors predicting the risk for osteoporosis. - Baatjes, Karin Jeanné (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.